Alternative treatment of resistant hypoparathyroidism by intermittent infusion of teriparatide using an insulin pump: A case report - Pekkolay, Zafer; Kilinc, Faruk; Soylu, Hikmet; Balsak, Belma; Guven, Mehmet; Tuzcu, Sadiye Altun; Tuzcu, Alpaslan Kemal (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2019)
Hypoparathyroidism usually responds to oral active vitamin D and calcium, but, although rare, some patients do not respond to this treatment. A 47-year-old Caucasian female presented to our medical unit with classical oral treatment-resistant hypocalcemia after thyroidectomy. Teriparatide was infused through the insulin pump with dosage set to 1 unit which equals to 2.5 mu g of teriparatide. In conclusion, intermittent subcutaneous infusion of teriparatide using an insulin pump is a safe and effective treatment modality to ensure normocalcemic conditions in patients with classical treatment-resistant hypoparathyroidism.
39th Turkey Congress of Endocrinology and Metabolic Diseases -- MAY 03-07, 2017 -- Antalya, TURKEY
Keywords: Hypoparathyroidism; pump infusion; teriparatide